Planting density on roses cultivars 'Avalanche' and 'Carola' in Lages-SC - Bastos F.E.A.* (2017)
The objective of this work was to evaluate the productivity of the Avalanche and Carola roses cultivars, with white and red color, respectively, in three planting densities in the municipality of Lages-SC. The experiment was implemented at the Santa Catarina State University campus (UDESC), spacing 1.0 m between rows and 30, 40 and 50 cm between plants, totaling 168 m2 of experiment in a protected environment. During harvesting the stems were cut with the largest possible stem length, leaving one yolk for the next budding. The evaluated variables were: flower stems production per plant, yield per area (floral stems / m2), floral stem mass (g), stem length (cm), floral button length (cm). The treatments consisted of two roseberry cultivars: Avalanche and Carola and three planting densities: 2.2, 2.5 and 3.3 plants per m2. In each block, treatments were arranged at random, organized into subdivided plots. The plots were the cultivars and the subplots were the planting densities. Each subplot was composed of six plants, totaling 18 plants per plot and 144 plants throughout the experiment. The density of 3.3 plants / m2 increased yield per growing area, without interfering in the quality of the floral stems of the cultivars Avalanche and Carola. The cultivar Carola produces longer flower stems than the cultivar Avalanche.